Effect of Metformin on Cardiac Metabolism and Longevity in Aged Female Mice - Zhu, Xudong; Shen, Weiyan; Liu, Zhu; Sheng, Shihao; Xiong, Wei; He, Ruikun; Zhang, Xuguang; Ma, Likun; Ju, Zhenyu (Frontiers in Cell and Developmental Biology, 2021)
The antidiabetic drug metformin exerts pleiotropic effects on multiple organs, including the cardiovascular system. Evidence has shown that metformin improves healthspan and lifespan in male mice, yet its lifespan lengthening effect in females remains elusive. We herein demonstrated that metformin fails to extend the lifespan in female mice. Compared to 2-month-old young controls, 20-month-old female mice showed a spectrum of degenerative cardiac phenotypes alongside significant alterations in the extracellular matrix composition. Despite lowered reactive oxygen species production, long-term metformin treatment did not improve cardiac function in the aged female mice. In contrast, RNA sequencing analyses demonstrated that metformin treatment elevated the extracellular matrix-related gene while lowering oxidative phosphorylation-related gene expression in the heart. In addition, metformin treatment induced metabolic reprogramming that suppressed mitochondrial respiration but activated glycolysis (i.e., Warburg effect) in cultured primary cardiomyocytes and macrophages, thereby sustaining an inflammatory status and lowering ATP production. These findings suggest the unexpected detrimental effects of metformin on the regulation of cardiac homeostasis and longevity in female mice, reinforcing the significance of comprehensive testing prior to the translation of metformin-based novel therapies.